Няня для принцессы: повесть / Ольга Хмельницкая - Хмельницкая Ольга (Няня-детектив, 2010)
Экземпляры: ф-5 (20180321) / Инвентарный номер: 51884 / Цена: 30.00 / Сис.шифр: Р2 / Авт.знак: Х 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4